On Micro-Buckling of Unidirectional Fiber-Reinforced Composites by Means of Computational Micromechanics - Néstor D. Barulich; Luis A. Godoy; Ever J. Barbero (Latin American Journal of Solids and Structures)
Abstract Micro-buckling of unidirectional fiber-reinforced composites is investigated in this paper by means of an explicit representation of a geometrically imperfect fiber within the context of kinematical and material non-linear behavior. Two types of fiber imperfections are considered: a helicoidal shape, identified as 3D imperfection; and a sinusoidal plane shape (2D imperfection). Both imperfection models are characterized by a maximum misalignment angle of the fiber with respect to the ideal or perfect configuration, as is usually considered in this field. A total of 816 cases were computed in terms of imperfection type (either 2D or 3D), fiber volume fraction, fiber arrangement (square or hexagonal array), orientation for 2D models, matrix yield stress, and misalignment angle. Two load cases, with constrained and unconstrained transverse strain, were considered. Assuming periodic boundary conditions, homogenization was carried out to obtain macroscopic stresses. Numerical results are compared with an analytical model available in the literature. The results show a high imperfection-sensitivity for small misalignment angles; on the other hand, the type of imperfection and the fiber arrangement do not have a large influence on the results. In addition, it was found that this problem is governed by fiber volume fraction and matrix yield stress only for small imperfections, whereas for large misalignment angles, a change in fiber volume fraction produces small changes in micro-buckling stress.